Novel solar cell and method for preparing light conversion component thereof

By using micro-nano-optical crystal material embedded in transparent protective spheres as the photoconversion layer of solar cells, the problems of low photoelectric conversion efficiency and poor material reliability of existing solar cells are solved, and efficient and stable photoelectric conversion effect is achieved.

CN115347069BActive Publication Date: 2025-03-04SHENZHEN MICRONANO OPTICAL CRYSTAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211026701.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-25
Publication Date
2025-03-04
Estimated Expiration
2042-08-25

AI Technical Summary

Technical Problem

The existing solar cells have low photoelectric conversion efficiency and the materials are sensitive to water and oxygen, resulting in poor reliability, which limits their application in the field of solar cell technology.

Method used

The micro-nano-optical crystal material of nanoluminescent material particles in transparent protective spheres is used to form a core material of the light conversion layer, and combined with the ITO protective layer and nano-AZO configuration, an efficient photoelectric conversion component is formed.

Benefits of technology

The photoelectric conversion efficiency of solar cells has been significantly improved to about 66%, and at the same time, the problem of nano-semiconductor materials' sensitivity to water and oxygen is solved, reducing production costs and manufacturing complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115347069B_ABST
    Figure CN115347069B_ABST
Patent Text Reader

Abstract

The present invention provides a solar cell, which includes a light conversion component, wherein the light conversion component includes a substrate, a light conversion layer including a micro-nano optical crystal material disposed on one side of the substrate, and an ITO protective layer covering the light conversion layer, wherein the substrate is an aluminum plate or an ITO PI film, and the ITO protective layer is an ITO glass or an ITO PI film. The light conversion layer includes micro-nano optical crystals and nano-AZO, wherein the configuration ratio of the micro-nano optical crystals to the nano-AZO is 5:1. The light conversion component based on the micro-nano optical crystals solves the problems of low luminous efficiency and high energy consumption of current solar cell photovoltaic components, and because it effectively solves the inherent reliability problem of quantum dot materials, the light conversion component reduces production costs while improving light conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cells, in particular to a method for preparing a solar cell based on a novel nano-luminescent semiconductor material and a light conversion component thereof. Background Art

[0002] At present, solar cells are mainly divided into two categories in terms of technology. One is inorganic solid-state solar cells based on the carrier transport process in semiconductor pn junctions, and the other is photoelectrochemical solar cells based on photoelectrochemical processes in organic molecular materials. Single-crystal GaAs solar cells, crystalline silicon solar cells, and silicon-based thin-film solar cells belong to the former category, while dye-sensitized solar cells and polymer solar cells belong to the latter category. The former type of solar cells has been industrialized or commercialized, while the latter type of solar cells is under research and development. The above-mentioned solar cells have the disadvantages of high energy consumption and low photoelectric conversion efficiency. Although the industry has adopted various methods to improve the conversion efficiency of the above-mentioned solar cells, it has not been able to significantly improve its photoelectric conversion efficiency.

[0003] Improving the energy conversion efficiency of solar cells has become a major topic in materials physics, photovoltaic devices and energy science. Finding new semiconductor materials that can significantly improve the photoelectric conversion rate of solar cells has become an important direction.

[0004] Among the existing luminescent semiconductor materials, nano-semiconductor luminescent materials mainly refer to quantum dots, including cadmium quantum dots, indium phosphide quantum dots and perovskite quantum dots, etc. The particle size of the material is between 2 and 15nm, the spectrum is adjustable (480nm to 635nm), and the half-wave width-FWHM is less than 25nm. The development and application prospects are relatively broad. The quantum dots refer to nanostructures whose dimensions in three dimensions are smaller than the de Broglie wavelength of the excitons of the corresponding bulk material. Theoretical studies have pointed out that quantum dot solar cells designed and manufactured using quantum dots with significant quantum confinement effects and discrete spectral characteristics as active regions can achieve extraordinary improvements in their energy conversion efficiency, and their limit value can reach about 66%, while the photoelectric conversion efficiency of the mainstream crystalline silicon technology of solar cells is theoretically only 30% at most. Due to the sensitivity of quantum dots to water and oxygen, it has not yet produced such a practical solar cell with ultra-high conversion efficiency, but a large number of theoretical calculations and experimental studies have confirmed that quantum dot solar cells will show great development prospects in future solar energy conversion.

[0005] The above-mentioned nano-semiconductor luminescent materials are very sensitive to water oxygen (water molecules and oxygen molecules) and have poor reliability, which has always been a major obstacle to their application in the field of solar cell technology. Therefore, the development of a new material battery that can significantly improve the photoelectric conversion efficiency of solar cells and ensure the high stability of semiconductor materials is the main research and development direction. Summary of the invention

[0006] The present invention provides a solar cell, which includes a light conversion component, the light conversion component includes a substrate, a light conversion layer including a micro-nano optical crystal material disposed on one side of the substrate, and an ITO protective layer covering the light conversion layer, wherein the micro-nano optical crystal material is a semiconductor material formed by physically and chemically embedding nano-luminescent material particles in a water-proof and oxygen-proof and transparent protective sphere with a particle size range of 0.1 micron to 15 micron. The substrate is an aluminum plate or an ITOPI film, and the ITO protective layer is an ITO glass or an ITO PI film. The light conversion layer includes micro-nano optical crystals and nano-AZO, wherein the configuration ratio of the micro-nano optical crystals to the nano-AZO is 5:1.

[0007] The substrate and the ITO protective layer play a role in protecting the light conversion layer sandwiched therebetween and in conducting current. The light conversion layer containing the micro-nano optical crystals is a photoelectric conversion unit.

[0008] The micro-nano optical crystal refers to a high-reliability semiconductor material that is made by embedding nano-luminescent materials (quantum dots) in a water-proof and oxygen-proof and transparent protective sphere with a particle size range of 0.1 micron to 15 microns through physical and chemical methods. The water-proof and oxygen-proof transparent sphere is made of organic and inorganic compounds such as polyvinyl alcohol, antioxidants, light stabilizers, caprolactam, and fumed silica in a certain proportion.

[0009] Since the luminescent core of the micro-nano optical crystal material is still based on nano-luminescent materials (not limited to cadmium quantum dots, indium phosphide quantum dots and perovskite quantum dots, etc.), its optical properties are basically the same as those of existing nano-luminescent materials, that is, its spectrum is pure, the half-wave width (FWHM) is less than 25nm, and the spectrum can be freely adjusted between 480nm and 635nm as needed; and since the particle size range of the micro-nano optical crystal material is different from that of quantum dots, which is between 0.1 microns and 15 microns, and different raw materials are used through different processes to prepare transparent small balls covering the periphery of quantum dots, this material has the advantage of high reliability of micron-luminescent materials, and at the same time, it does not require the expensive auxiliary materials required in the preparation and use of existing nanomaterials, thereby greatly reducing the preparation and use costs of luminescent materials with better performance.

[0010] The raw materials for preparing micro-nano optical crystals include: polyvinyl alcohol (PVA, molecular formula -[C 2 H 4O]n), antioxidants, light stabilizers, caprolactam, fumed silica, etc., wherein the antioxidant includes dimethylbenzene dibutylbenzofuranone (molecular formula -C 24 H 30 O 2 ), triphosphite (molecular formula -C 42 H 63 O 3 P), pentaerythritol ester (molecular formula -C 73 H 108 O 12 )、1,3,5-trimethyl-2,4,6-benzene (molecular formula -C 54 H 78 O 3 ), etc., the light stabilizer includes a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol (molecular formula -(C 15 H 25 NO 4 ) n .CH 4 O), the chemical formula of caprolactam is C 6 H 11 NO.

[0011] The preparation steps of micro-nano optical crystals are as follows:

[0012] Step 1: Preparation of solution A: Mix the above raw materials at a ratio of PVA: water: caprolactam = 5:5:1 through a rubber mixer at 2000 rpm for 3 to 5 minutes, then swell into a viscous liquid at a temperature of 150° C., and then mix through a rubber mixer at 2000 rpm for 3 to 5 minutes to form solution A for use;

[0013] Step 2: Preparation of mixture B, according to dimethylbenzene dibutylbenzofuranone (molecular formula -C 24 H 30 O 2 ): triphosphite (molecular formula -C 42 H 63 O 3 P): Pentaerythritol ester (molecular formula -C 73 H 108 O 12 ):1,3,5-trimethyl-2,4,6-benzene (molecular formula -C 54 H 78 O 3 ): polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol (molecular formula -(C 15 H 25 NO 4 ) n .CH 4O): fumed silica = 5:3:2:1:2:1 configuration ratio The above raw materials are mixed in a rubber mixer at 1500 rpm for 3 minutes to form a mixture B for use;

[0014] Step 3: Preparation of C nano-luminescent material mixture, purifying and re-dissolving the nano-luminescent material solution, and re-preparing the required solution with a concentration of 50 OD to 100 OD / g (50 mg to 100 mg / g) in toluene or n-hexane as the solvent, and set aside;

[0015] Step 4: Preparation of mixture D: the A solution prepared in step 1 and step 2 and the mixture B are prepared in a ratio of A:B=200:1, and mixed by a rubber mixer at 2000 rpm for 5 to 8 minutes to form a mixture D for later use;

[0016] Step 5: Preparation of mixture E: the mixture of nano-luminescent materials C prepared in step 3 and step 4 and the mixture D are mixed in a ratio of C:D=(1-2):1, and mixed by a rubber mixer at 2000 rpm-2500 rpm for 5-8 minutes to form a mixture E;

[0017] Step 6: Prepare the rough micro-nano optical crystal (F mixture), which is divided into the following steps:

[0018] a) Place the above E mixture in a vacuum high temperature oven, set the temperature at 85 degrees, and evacuate until the vacuum degree reaches -100Pa and remains stable within 5 minutes;

[0019] b) Fill the vacuum high temperature oven with inert gas to normal pressure, then evacuate to -100Pa, repeat this cycle 3 times or more, and finally keep the vacuum degree in the vacuum high temperature oven at -100Pa;

[0020] c) Set the temperature in stages as follows: 90°C for 10 minutes - 140°C for 5 minutes - 170°C for 3 minutes - 190°C for 3 minutes, heat at this set temperature, and evacuate during the process, keeping the vacuum degree at -100Pa;

[0021] d) filling with inert gas to normal pressure and cooling to room temperature;

[0022] e) Heat treatment, set the temperature in stages as follows: 100°C for 5 minutes - 150°C for 5 minutes - 200°C for 3 minutes - 120°C for 5 minutes, heat at this set temperature, and evacuate during the process to maintain the vacuum degree at -100Pa;

[0023] f) filling with inert gas to normal pressure and cooling to room temperature to form a mixture F;

[0024] Step 7: Prepare micro-nano optical crystals (G mixture), which is divided into the following steps:

[0025] a) Grinding the F mixture (micro-nano optical crystal rough embryo) obtained in step 6 (not limited to airflow grinding, mechanical impact grinding, etc.) to obtain micro-nano optical crystal particles of 0.1 micron to 15 micron, and sieving and classifying them through sieves of different mesh sizes;

[0026] b) placing the micro-nano optical crystal powder material obtained in a) above in a high temperature oven, heating it to 75° C. and keeping it for 15 minutes;

[0027] c) Obtain the final product G mixture - micro-nano optical crystals.

[0028] There is no requirement for the order of the above preparation steps 1 to 3, and they can also be carried out simultaneously.

[0029] The photoelectric properties of micro-nano optical crystals are the same as those of quantum dots. They have a nanostructure with the de Broglie wavelength of the excitons of the corresponding bulk material, and have a significant quantum confinement effect and discrete spectral characteristics, which can make their energy conversion efficiency extraordinary. The limit value can reach about 66%, while the photoelectric conversion efficiency of the mainstream crystalline silicon technology of solar cells is theoretically only 30% at most (mainly because quantum dots have a much larger wavelength range for effectively receiving or absorbing sunlight than silicon), and it also solves the sensitivity of quantum dots to water and oxygen. The light conversion component based on the micro-nano optical crystal solves the problems of low luminous efficiency and high energy consumption of the current solar cell photovoltaic components, and because it effectively solves the inherent reliability problem of quantum dot materials, the light conversion component reduces production costs while improving light conversion efficiency.

[0030] In addition, compared with traditional silicon-based solar cells, it does not require a hole transport layer and an electron transport layer. While having a simple and optimized structure, it greatly simplifies the manufacturing process, greatly improving the light conversion efficiency while reducing the manufacturing cost.

[0031] The existing perovskite quantum dot solar cells need to be manufactured simultaneously with the manufacture of perovskite quantum dots during the manufacturing process, that is, the manufacturing process of perovskite quantum dots must be integrated into the manufacturing process of perovskite quantum dot solar cells. The production time requirements are relatively tight and the production space is not flexible enough. Because it also requires a hole transport layer and an electron transport layer, its manufacturing cost is also high. In addition, although its photoelectric conversion efficiency is high, its stability or reliability is very poor, resulting in a short product life and high cost of use.

[0032] Compared with traditional silicon-based solar cells and existing perovskite quantum dot solar cells, the solar cells based on micro-nano optical crystals provided by the present invention have unique advantages, namely, simple structure and process, low manufacturing and use costs, low energy consumption, and high photoelectric conversion efficiency.

[0033] The steps for preparing the above-mentioned light conversion component as a rigid light conversion component are as follows:

[0034] Step 1, preparation of A1 mixture: prepare the mixture in a ratio of micro-nano optical crystal to AZO = 5:1, mix it with a glue mixer at 2000 rpm for 3 to 5 minutes, and then mix it with a glue mixer at 2500 rpm for 3 to 5 minutes;

[0035] Step 2, preparation of B1 solution: A1 mixture: n-hexane = 1:10 ratio, mixed by a rubber mixer at 2000 rpm for 3 to 5 minutes, and then mixed by a rubber mixer at 2500 rpm for 3 to 5 minutes;

[0036] Step 3, preparation of a rigid light conversion component, includes the following steps:

[0037] a) The aluminum sheet is subjected to the following surface treatment: water cleaning --- neutral solvent cleaning --- water cleaning, drying, sandblasting (2000 mesh), water cleaning --- neutral solvent cleaning --- water cleaning, drying;

[0038] b) applying the B1 solution evenly on the treated thin aluminum plate by blade coating, with the thickness controlled at 10 μm;

[0039] c) placing the aluminum plate coated with the B1 solution in a vacuum high-temperature oven, setting the temperature at 45° C., and starting to evacuate until the vacuum degree reaches -100 Pa and remains stable within 5 minutes;

[0040] d) Cover the ITO glass on the aluminum plate (the ITO surface is in contact with the micro-nano optical crystal);

[0041] e) Filling nitrogen into the vacuum high temperature oven to normal pressure and then evacuating to -100Pa, repeating this cycle 3 times, and finally maintaining the vacuum degree in the vacuum high temperature oven at -100Pa;

[0042] f) Set the temperature in stages as follows: 90°C for 1 minute - 190°C for 1 minute - 150°C for 3 minutes - 100°C for 1 minute, and heat continuously at the set temperature. During this process, evacuate the air and keep the vacuum degree at -100Pa;

[0043] g) filling with nitrogen to normal pressure and cooling to room temperature;

[0044] h) Cutting into required shapes and sizes as needed to obtain the required rigid light conversion components.

[0045] The steps for preparing the above-mentioned light conversion component as a flexible light conversion component are as follows:

[0046] Step 1, preparation of A1 mixture: prepare the mixture in a ratio of micro-nano optical crystal to AZO = 5:1, mix it with a glue mixer at 2000 rpm for 3 to 5 minutes, and then mix it with a glue mixer at 2500 rpm for 3 to 5 minutes;

[0047] Step 2, preparation of B1 solution: A1 mixture: n-hexane = 1:10 ratio, mixed by a rubber mixer at 2000 rpm for 3 to 5 minutes, and then mixed by a rubber mixer at 2500 rpm for 3 to 5 minutes;

[0048] Step 3, preparation of the flexible light conversion component, including the following steps:

[0049] a) applying the B1 solution evenly on the treated ITO PI film by blade coating, with the thickness controlled at 10 μm;

[0050] b) placing the ITO PI film coated with the B1 solution in a vacuum high-temperature oven, setting the temperature at 45° C., and starting to evacuate until the vacuum degree reaches -100 Pa and remains stable within 5 minutes;

[0051] c) Covering the new (additional) ITO PI film on the ITO PI film coated with the micro-nano optical crystal (the ITO surface is in contact with the micro-nano optical crystal);

[0052] d) Filling nitrogen into the vacuum high temperature oven to normal pressure and then evacuating to -100 Pa, repeating this cycle 3 times, and finally maintaining the vacuum degree in the vacuum high temperature oven at -100 Pa;

[0053] e) Set the temperature in the following stages: 90°C for 1 minute - 190°C for 1 minute - 150°C for 3 minutes - 100°C for 1 minute, and heat continuously at the set temperature. During this process, evacuate the air and keep the vacuum degree at -100Pa;

[0054] f) filling with nitrogen to normal pressure and cooling to room temperature;

[0055] g) Cutting into required shapes and sizes as required to obtain the required flexible light conversion components.

[0056] From the preparation process of the light conversion component described above, it can be seen that compared with traditional solar cells and perovskite quantum dot solar cells, its preparation process is greatly simplified, the preparation process is more adaptable, and the manufacturing cost of the product is greatly reduced.

[0057] It should be noted that the "2000 rpm", "at a temperature of 150°C", "mixing for 3 minutes", "temperature set at 85 degrees", "vacuum reaches -100 Pa", "maintain vacuum at -100 Pa", "maintain at 90°C for 10 minutes" and so on described in this article involve parameters or ratios with clear specific numbers, which should be understood in the technical solution provided by the present invention as being near the above-mentioned values ​​that can be achieved by technical personnel in this field in actual operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 A comparison diagram of color point aging attenuation between the micro-nano optical crystal material embodiment 1 used in the present invention and the phosphor and quantum dot materials;

[0059] Figure 2 This is a comparison diagram of the color point aging attenuation of the micro-nano optical crystal material embodiment 2 used in the present invention and the phosphor and quantum dot materials;

[0060] Figure 3 This is a comparison diagram of the color point aging attenuation of the micro-nano optical crystal material embodiment 3 used in the present invention and the phosphor and quantum dot materials;

[0061] Figure 4 This is a comparison diagram of the brightness aging attenuation of the micro-nano optical crystal material embodiment 1 used in the present invention and the phosphor and quantum dot materials;

[0062] Figure 5 This is a comparison diagram of the brightness aging attenuation of the micro-nano optical crystal material embodiment 2 used in the present invention and the phosphor and quantum dot materials;

[0063] Figure 6 This is a comparison diagram of the brightness aging attenuation of the micro-nano optical crystal material embodiment 3 used in the present invention and the phosphor and quantum dot materials;

[0064] Figure 7 This is a schematic structural diagram of the light conversion component portion of a solar cell based on micro-nano optical crystal materials provided by the present invention. DETAILED DESCRIPTION

[0065] In order to more clearly illustrate the technical solution of the present invention, the embodiments of the present invention will be briefly described below in conjunction with the accompanying drawings. Obviously, the description of the embodiments and the accompanying drawings is only for illustrating the technical solution and technical effects of the present invention. In the context that ordinary technicians in the field can understand, the protection scope of the present invention is not limited to the embodiments and the accompanying drawings.

[0066] First, an introduction to an embodiment of the micro-nano optical crystal material used in the technical solution of the present invention is provided.

[0067] In the first embodiment, the particle size of the micro-nano optical crystal material particles is between 0.1 microns and 15 microns, and the core of the material particles is an existing nano-luminescent material particle, and the nano-luminescent material particle is embedded in a water-proof and oxygen-proof and transparent protective sphere.

[0068] The raw materials for preparing micro-nano optical crystals include, in addition to the necessary nano-luminescent materials, polyvinyl alcohol (PVA, molecular formula: 2 H 4 O]n), antioxidants, light stabilizers, caprolactam, fumed silica, etc., wherein the antioxidant includes dimethylbenzene dibutylbenzofuranone (molecular formula -C 24 H 30 O 2 ), triphosphite (molecular formula -C 42 H 63 O 3 P), pentaerythritol ester (molecular formula -C 73 H 108 O 12 )、1,3,5-trimethyl-2,4,6-benzene (molecular formula -C 54 H 78 O 3 ), etc., the light stabilizer includes a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol (molecular formula -(C 15 H 25 NO 4 ) n .CH 4 O), the chemical formula of caprolactam is C 6 H 11 NO.

[0069] The steps for preparing the micro-nano optical crystal are as follows:

[0070] Step 1: Preparation of solution A: Mix the above raw materials at a ratio of PVA: water: caprolactam = 5:5:1 through a rubber mixer at 2000 rpm for 3 to 5 minutes, then swell into a viscous liquid at a temperature of 150° C., and then mix through a rubber mixer at 2000 rpm for 3 to 5 minutes to form solution A for use;

[0071] Step 2: Preparation of mixture B, according to dimethylbenzene dibutylbenzofuranone (molecular formula -C 24 H 30 O 2 ): triphosphite (molecular formula -C 42 H 63 O 3 P): Pentaerythritol ester (molecular formula -C 73 H 108 O 12):1,3,5-trimethyl-2,4,6-benzene (molecular formula -C 54 H 78 O 3 ): polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol (molecular formula -(C 15 H 25 NO 4 ) n .CH 4 O): fumed silica = 5:3:2:1:2:1 configuration ratio The above raw materials are mixed in a rubber mixer at 1500 rpm for 3 minutes to form a mixture B for use;

[0072] Step 3: Preparation of C nano-luminescent material mixture, purifying and re-dissolving the nano-luminescent material solution, and re-preparing the required solution with a concentration of 50 OD to 100 OD / g (50 mg to 100 mg / g) in toluene or n-hexane as the solvent, and set aside;

[0073] The above three steps can be performed simultaneously or separately in any order.

[0074] Step 4: Preparation of mixture D: the A solution prepared in step 1 and step 2 and the mixture B are prepared in a ratio of A:B=200:1, and mixed by a rubber mixer at 2000 rpm for 5 to 8 minutes to form a mixture D for later use;

[0075] Step 5: Preparation of mixture E: the mixture of nano-luminescent materials C prepared in step 3 and step 4 and the mixture D are mixed in a ratio of C:D=1:1, and mixed by a rubber mixer at 2000 rpm to 2500 rpm for 5 to 8 minutes to form a mixture E;

[0076] Step 6: Prepare the rough micro-nano optical crystal (F mixture), which is divided into the following steps:

[0077] a) Place the above E mixture in a vacuum high temperature oven, set the temperature at 85 degrees, and evacuate until the vacuum degree reaches -100Pa and remains stable within 5 minutes;

[0078] b) Fill the vacuum high temperature oven with nitrogen to normal pressure, then evacuate to -100Pa, repeat this process 3 times or more (the purpose is to remove oxygen, in practice, the deoxygenation effect is not significantly increased if the cycle is repeated more than 3 times), and finally keep the vacuum degree in the vacuum high temperature oven at -100Pa;

[0079] c) Set the temperature in stages as follows: 90°C for 10 minutes - 140°C for 5 minutes - 170°C for 3 minutes - 190°C for 3 minutes, heat at this set temperature, and evacuate during the process, keeping the vacuum degree at -100Pa;

[0080] d) filling with nitrogen to normal pressure and cooling to room temperature;

[0081] e) Heat treatment, set the temperature in stages as follows: 100°C for 5 minutes - 150°C for 5 minutes - 200°C for 3 minutes - 120°C for 5 minutes, heat at this set temperature, and evacuate during the process to maintain the vacuum degree at -100Pa;

[0082] f) filling with nitrogen to normal pressure and cooling to room temperature to form a mixture F;

[0083] Step 7: Prepare micro-nano optical crystals (G mixture), which is divided into the following steps:

[0084] a) Grinding the F mixture (micro-nano optical crystal rough embryo) obtained in step 6 by air flow to obtain micro-nano optical crystal particles of 0.1 μm to 15 μm, and sieving and classifying them through sieves of different mesh sizes;

[0085] b) placing the micro-nano optical crystal powder material obtained in a) above in a high temperature oven, heating it to 75° C. and keeping it for 15 minutes;

[0086] c) Obtain the final product G mixture - micro-nano optical crystals.

[0087] The difference between Example 2 and Example 1 is that in the preparation step 5, C:D=3:2, and the grinding method in step 7 is mechanical impact grinding, and the rest are the same.

[0088] The difference between Example 3 and Example 1 is that in the preparation step 5, C:D=2:1, and the grinding method in step 7 is mechanical impact grinding, and the rest are the same.

[0089] The micro-nano optical crystal material (MNC) prepared in the above embodiment is made into a micro-nano optical crystal chip (MNC-DIE), and then the chip is made into a micro-nano optical crystal LED (MNC-LED), with a power of 0.5W and a package specification of 3030 (6V, 80 mA). At room temperature and the same specification of phosphor LED, quantum dot LED (same color point, same package specification) are lit under the same current and voltage, and their color point (X, Y color point coordinate numerical attenuation) and brightness (LV numerical attenuation) are tested, as shown in the attached figure. Figure 1-6 shown.

[0090] By the attached Figure 1-3 It can be seen that the aging attenuation of the color point of the micro-nano optical crystal material in the two time periods of 1000 hours and 4056 hours is basically consistent with that of the phosphor, which is significantly better than the attenuation of the quantum dot material.

[0091] By the attached Figure 4-6It can be seen that the brightness of the micro-nano optical crystal material ages and decays in the two time periods of 1000 hours and 4056 hours. The brightness aging decay of the micro-nano optical crystal is basically consistent with that of the phosphor in the time period of 1000 hours, and is slightly worse than the phosphor in the time period of 4056 hours (about 15%), but basically remains stable. At the same time, it is significantly better than the brightness decay of quantum dot materials.

[0092] According to the comparative tests of the above embodiments, it can be seen that the micro-nano optical crystals have the advantages of quantum dot optical properties while eliminating the shortcomings of instability or low reliability of quantum dot materials; at the same time, the micro-nano optical crystals are comparable to phosphors in stability, while their unique quantum dot optical properties are superior to phosphors.

[0093] The following will introduce the embodiments of the light conversion components based on the above-mentioned micro-nano optical crystal materials. Embodiment 01 is a solar cell including a rigid light conversion component. The solar cell includes a light conversion component such as Figure 7 As shown, the light conversion component includes a substrate 3, a light conversion layer 2 containing micro-nano optical crystal material arranged on one side of the substrate 3, and an ITO protective layer 1 covering the light conversion layer, the substrate 3 is an aluminum plate, the ITO protective layer is ITO glass, the light conversion layer 2 contains micro-nano optical crystals and nano-AZO, wherein the configuration ratio of the micro-nano optical crystals to the nano-AZO is 5:1.

[0094] The steps for preparing the light conversion component in Example 01 are as follows:

[0095] Step 1, preparation of A1 mixture: prepare the mixture in a ratio of micro-nano optical crystal to AZO = 5:1, mix it with a glue mixer at 2000 rpm for 3 to 5 minutes, and then mix it with a glue mixer at 2500 rpm for 3 to 5 minutes;

[0096] Step 2, preparation of B1 solution: A1 mixture: n-hexane = 1:10 ratio, mixed by a rubber mixer at 2000 rpm for 3 to 5 minutes, and then mixed by a rubber mixer at 2500 rpm for 3 to 5 minutes;

[0097] Step 3, preparation of a rigid light conversion component, includes the following steps:

[0098] a) The aluminum sheet is subjected to the following surface treatment: water cleaning --- neutral solvent cleaning --- water cleaning, drying, sandblasting (2000 mesh), water cleaning --- neutral solvent cleaning --- water cleaning, drying;

[0099] b) applying the B1 solution evenly on the treated thin aluminum plate by blade coating, with the thickness controlled at 10 μm;

[0100] c) placing the aluminum plate coated with the B1 solution in a vacuum high-temperature oven, setting the temperature at 45° C., and starting to evacuate until the vacuum degree reaches -100 Pa and remains stable within 5 minutes;

[0101] d) Cover the ITO glass on the aluminum plate (the ITO surface is in contact with the micro-nano optical crystal);

[0102] e) Filling nitrogen into the vacuum high temperature oven to normal pressure and then evacuating to -100Pa, repeating this cycle 3 times, and finally maintaining the vacuum degree in the vacuum high temperature oven at -100Pa;

[0103] f) Set the temperature in stages as follows: 90°C for 1 minute - 190°C for 1 minute - 150°C for 3 minutes - 100°C for 1 minute, and heat continuously at the set temperature. During this process, evacuate the air and keep the vacuum degree at -100Pa;

[0104] g) filling with nitrogen to normal pressure and cooling to room temperature;

[0105] h) Cutting into required shapes and sizes as needed to obtain the required rigid light conversion components.

[0106] Embodiment 02 is a solar cell comprising a flexible light conversion component. The solar cell comprises a light conversion component such as Figure 7 As shown, the light conversion component includes a substrate 3, a light conversion layer 2 containing micro-nano optical crystal material arranged on one side of the substrate 3, and an ITO protective layer 1 covering the light conversion layer, the substrate 3 is an ITO PI film, the ITO protective layer is an ITO PI film, the light conversion layer 2 contains micro-nano optical crystals and nano-AZO, wherein the configuration ratio of the micro-nano optical crystals to the nano-AZO is 5:1.

[0107] The steps for preparing the light conversion component in Example 02 are as follows:

[0108] Step 1, preparation of A1 mixture: prepare the mixture in a ratio of micro-nano optical crystal to AZO = 5:1, mix it with a glue mixer at 2000 rpm for 3 to 5 minutes, and then mix it with a glue mixer at 2500 rpm for 3 to 5 minutes;

[0109] Step 2, preparation of B1 solution: A1 mixture: n-hexane = 1:10 ratio, mixed by a rubber mixer at 2000 rpm for 3 to 5 minutes, and then mixed by a rubber mixer at 2500 rpm for 3 to 5 minutes;

[0110] Step 3, preparation of the flexible light conversion component, including the following steps:

[0111] a) applying the B1 solution evenly on the treated ITO PI film by blade coating, with the thickness controlled at 10 μm;

[0112] b) placing the ITO PI film coated with the B1 solution in a vacuum high-temperature oven, setting the temperature at 45° C., and starting to evacuate until the vacuum degree reaches -100 Pa and remains stable within 5 minutes;

[0113] c) Covering the new ITO PI film on the ITO PI film coated with the micro-nano optical crystal (the ITO surface is in contact with the micro-nano optical crystal);

[0114] d) Filling nitrogen into the vacuum high temperature oven to normal pressure and then evacuating to -100 Pa, repeating this cycle 3 times, and finally maintaining the vacuum degree in the vacuum high temperature oven at -100 Pa;

[0115] e) Set the temperature in stages as follows: 90°C for 1 minute - 190°C for 1 minute - 150°C for 3 minutes - 100°C for 1 minute, and heat continuously at the set temperature. During this process, evacuate the air and keep the vacuum degree at -100Pa;

[0116] f) filling with nitrogen to normal pressure and cooling to room temperature;

[0117] g) Cutting into required shapes and sizes as required to obtain the required flexible light conversion components.

[0118] The above-prepared light conversion components are used as the main photovoltaic components to manufacture solar cells. This type of solar cell based on micro-nano optical crystal light conversion components has the advantages of low energy consumption, high photoelectric conversion rate, and low manufacturing and use costs, and has broad prospects for development and promotion.

[0119] The above embodiments are only used to illustrate the technical solutions of the present invention and should not be considered as limiting the protection scope of the present invention. In addition to being used in the field of solar cells, the present invention can also be applied to any other similar fields such as lighting and display.

Claims

1. A solar cell, comprising a photoelectric conversion component, characterized in that: The photoelectric conversion component includes a substrate, a photoelectric conversion layer containing a semiconductor light-emitting material disposed on one side of the substrate, and an ITO protective layer covering the photoelectric conversion layer. The semiconductor light-emitting material is a micro-nano optical crystal. The micro-nano optical crystal material is a semiconductor material formed by physically and chemically embedding nano-luminescent material particles in a water-proof and oxygen-proof and transparent protective sphere with a particle size range of 0.1 micron to 15 micron. The photoelectric conversion layer contains the micro-nano optical crystal and nano-AZO.

2. The solar cell according to claim 1, wherein: The substrate is an aluminum plate or an ITO PI film.

3. The solar cell according to claim 1, wherein: The ITO protective layer is ITO glass or ITO PI film.

4. The solar cell according to claim 1, wherein: The configuration ratio of the micro-nano optical crystal to the nano-AZO is 5:

1.

5. The solar cell according to claim 1, wherein: The protective sphere is prepared from polyvinyl alcohol, antioxidant, light stabilizer, caprolactam and fumed silica in the following ratio: polyvinyl alcohol: antioxidant: light stabilizer: caprolactam: fumed silica = 1000:11:2:200:

1.

6. The solar cell according to claim 5, characterized in that The antioxidant includes dimethylbenzene dibutylbenzofuranone (molecular formula -C 24 H 30 O2), triphosphite (molecular formula -C 42 H 63 O3P), pentaerythritol ester (molecular formula -C 73 H 108 O 12 )、1,3,5-trimethyl-2,4,6-benzene (molecular formula -C 54 H 78 O3), each of the antioxidants is configured in the following proportions: dimethylbenzene dibutylbenzofuranone (molecular formula -C 24 H 30 O2): triphosphite (molecular formula -C 42 H 63 O3P): Pentaerythritol ester (molecular formula -C 73 H 108 O 12 ):1,3,5-trimethyl-2,4,6-benzene (molecular formula -C 54 H 78 O3)=5:3:2:

1.

7. The solar cell according to claim 5, characterized in that The light stabilizer is a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol (molecular formula: 15 H 25 NO4) n .CH4O).

8. The solar cell according to any one of claims 1 to 7, characterized in that: The method for preparing the photoelectric conversion component comprises the following steps: Step 1, preparation of A1 mixture: prepare the mixture in a ratio of micro-nano optical crystal to AZO = 5:1, mix it with a glue mixer at 2000 rpm for 3 to 5 minutes, and then mix it with a glue mixer at 2500 rpm for 3 to 5 minutes; Step 2, preparation of B1 solution: the A1 mixture: n-hexane = 1:10 ratio is prepared, mixed by a rubber mixer at 2000 rpm for 3 to 5 minutes, and then mixed by a rubber mixer at 2500 rpm for 3 to 5 minutes; Step 3, preparation of a rigid photoelectric conversion component, comprising the following steps: a) The aluminum plate is surface treated in the following order: water cleaning --- neutral solvent cleaning --- water cleaning, drying, sandblasting, water cleaning --- neutral solvent cleaning --- water cleaning, drying; b) evenly coating the B1 solution on the treated thin aluminum plate with a thickness of 10 μm; c) placing the thin aluminum plate coated with the B1 solution in a vacuum high-temperature oven, setting the temperature at 45° C., and starting to evacuate until the vacuum degree reaches -100 Pa and remains stable within 5 minutes; d) Covering the ITO glass on a thin aluminum plate, with the ITO surface in contact with the B1 solution; e) Filling nitrogen into the vacuum high temperature oven to normal pressure and then evacuating to -100Pa, repeating this cycle 3 times, and finally maintaining the vacuum degree in the vacuum high temperature oven at -100Pa; f) Set the temperature in stages as follows: 90°C for 1 minute - 190°C for 1 minute - 150°C for 3 minutes - 100°C for 1 minute, and heat continuously at the set temperatures. During this process, evacuate the air and keep the vacuum degree at -100Pa; g) filling with nitrogen to normal pressure and cooling to room temperature; h) Cutting into required shapes and sizes as required to obtain the required rigid photoelectric conversion components.

9. The solar cell according to any one of claims 1 to 7, characterized in that: The method for preparing the photoelectric conversion component comprises the following steps: Step 1, preparation of A1 mixture: prepare the mixture in a ratio of micro-nano optical crystal to AZO = 5:1, mix it with a glue mixer at 2000 rpm for 3 to 5 minutes, and then mix it with a glue mixer at 2500 rpm for 3 to 5 minutes; Step 2, preparation of B1 solution: the A1 mixture: n-hexane = 1:10 ratio is prepared, mixed by a rubber mixer at 2000 rpm for 3 to 5 minutes, and then mixed by a rubber mixer at 2500 rpm for 3 to 5 minutes; Step 3, preparation of a flexible photoelectric conversion component, comprising the following steps: a) evenly coating the B1 solution on the treated ITO PI film with a thickness of 10 μm; b) placing the ITO PI film coated with the B1 solution in a vacuum high-temperature oven, setting the temperature at 45° C., and starting to evacuate until the vacuum degree reaches -100 Pa and remains stable within 5 minutes; c) covering the new ITO PI film on the ITO PI film coated with the micro-nano optical crystals, with the ITO surface in contact with the B1 solution; d) Filling nitrogen into the vacuum high temperature oven to normal pressure and then evacuating to -100 Pa, repeating this cycle 3 times, and finally maintaining the vacuum degree in the vacuum high temperature oven at -100 Pa; e) Set the temperature in stages as follows: 90°C for 1 minute - 190°C for 1 minute - 150°C for 3 minutes - 100°C for 1 minute, and heat continuously at the set temperatures. During this process, evacuate the air and keep the vacuum degree at -100Pa; f) filling with nitrogen to normal pressure and cooling to room temperature; g) Cutting into required shapes and sizes according to needs to obtain the required flexible photoelectric conversion components.